2021
DOI: 10.1111/age.13161
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high‐resolution typing method for SLA‐3, swine MHC class I antigen 3

Abstract: We developed a high-resolution and comprehensive typing method for swine leukocyte antigen 3 (SLA-3), an MHC class I gene, employing locus-specific genomic PCR followed by subsequent direct sequencing. A total of 292 individuals from nine pure, one cross-breed and six cell lines were successfully typed. A total of 21 SLA-3 alleles were identified, of which four were found to be novel alleles. However, the allelic diversity of SLA-3 was lower than that of previously reported class I genes, SLA-1 and -2. More SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the genetic characteristics of the two protein families are similar. For swine leukocyte antigen (SLA) genes, which is the MHC genes of pig, it has been well documented that the presence of an extremely large number of alleles, a large difference in allelic constitution among different breeds, and breed-speci c alleles [42][43][44][45][46][47] are most likely to result from independent breeding histories for different breeds. In addition, the characteristics of pig OR genes analyzed in this current study showed similarities to those of the SLA genes described above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the genetic characteristics of the two protein families are similar. For swine leukocyte antigen (SLA) genes, which is the MHC genes of pig, it has been well documented that the presence of an extremely large number of alleles, a large difference in allelic constitution among different breeds, and breed-speci c alleles [42][43][44][45][46][47] are most likely to result from independent breeding histories for different breeds. In addition, the characteristics of pig OR genes analyzed in this current study showed similarities to those of the SLA genes described above.…”
Section: Discussionmentioning
confidence: 99%
“…However, MHC class I genes consisting of Patr-A, Patr-B, and Patr-C exhibit only 86% sequence identity to class I genes in humans [31][32][33]. Progress in understanding the genetic diversity of MHC systems of cattle and pigs, known as the bovine leukocyte antigen (BoLA) and swine leukocyte antigen (SLA), respectively, have also been made using comprehensive typing methods [18,30,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%